PORTRAYAL OF INDIAN WOMEN IN INDIAN ENGLISH NOVELS - Dr Dilip K Madhesiya (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2021)
Indians have been writing in English for decades now. Indian English Novels are contemporaries to the British, American, African, and even Common Wealth writings in English. Since people have written these novels about their own country, these books are a great mirror of contemporary society, which varies from nation to nation and possesses a common undercurrent to all countries: the condition of women in that era. Bankim Chandra Chatterjee, Nayantara Sahgal, Arundhati Roy, Vikram Seth, Raja Rao, Torudutt, Mulk Raj Anand, and Chetan Bhagat have written about women and their lives in their novels. It is clear from their writings what the condition of women was in the era of the respective writers. Naturally, the portrayal is not uniform. In this paper, I aim to find out differences in these portrayals and how accurate these images are- to the actual conditions of the women in that era. Keywords: Women, English, Indian Literature, Contemporary, Development